2020
DOI: 10.21203/rs.3.rs-88524/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beta-cells from patients with COVID-19 and from isolated human islets exhibit ACE2, DPP4, and TMPRSS2 expression, viral infiltration and necroptotic cell death

Abstract: Here we report a possible mechanistic link between coronavirus disease 2019 (COVID-19) and diabetes. In addition to its known role on the respiratory system, the human coronavirus SARS-CoV-2 has been shown to affect the endocrine system including the pancreas 1-4. It has been suggested that the virus can induce type 1 diabetes 5-8. Therefore, we isolated human pancreatic islets and examined the expression of angiotensin-converting enzyme 2 (ACE2) and the protease TMPRSS2, known to be important for SARS-CoV-2 e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…5,6 ); similar data were previously reported in patients affected by SARS-CoV-1, which has been shown to increase the levels of fasting glucose as compared to glucose levels observed in patients with pneumonia unrelated to SARS-CoV-1 infection [7][8][9] . Currently, little evidence exists as to whether the effect of SARS-CoV-2 on beta cell function is direct or indirect 10,11 . It is theoretically possible that SARS-CoV-2 may localize to the endocrine pancreas; indeed, mRNA levels of angiotensin-converting enzyme 2 (ACE2), which is the primary SARS-CoV-2 receptor, were found to be high in both exocrine and endocrine pancreas 8,12 , and immunohistochemistry as well as in situ hybridization studies have identified SARS-CoV-1-related antigen in the pancreases of patients who died of SARS-CoV-1 (refs.…”
mentioning
confidence: 99%
“…5,6 ); similar data were previously reported in patients affected by SARS-CoV-1, which has been shown to increase the levels of fasting glucose as compared to glucose levels observed in patients with pneumonia unrelated to SARS-CoV-1 infection [7][8][9] . Currently, little evidence exists as to whether the effect of SARS-CoV-2 on beta cell function is direct or indirect 10,11 . It is theoretically possible that SARS-CoV-2 may localize to the endocrine pancreas; indeed, mRNA levels of angiotensin-converting enzyme 2 (ACE2), which is the primary SARS-CoV-2 receptor, were found to be high in both exocrine and endocrine pancreas 8,12 , and immunohistochemistry as well as in situ hybridization studies have identified SARS-CoV-1-related antigen in the pancreases of patients who died of SARS-CoV-1 (refs.…”
mentioning
confidence: 99%